1999
DOI: 10.1093/ps/78.11.1542
|View full text |Cite
|
Sign up to set email alerts
|

Laying hen productivity as affected by energy, supplemental fat, and linoleic acid concentration of the diet

Abstract: A trial using 720 Isabrown hens was conducted to determine the influence of energy (AMEn), supplemental fat (SFAT), and linolenic acid (LIN) concentration of the diet on performance and weight of eggs and egg components throughout the laying cycle (22 to 65 wk of age). There were six treatments whose calculated AMEn, SFAT, and LIN content were, respectively: 1) 2,810 kcal/kg, 0%, 1.15%; 2) 2,810 kcal/kg, 4%, 1.15%; 3) 2,810 kcal/kg, 4%, 1.65%; 4) 2,680 kcal/kg, 0%, 1.15%; 5) 2,680 kcal/kg, 4%, 1.15%; and 6) 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
69
8
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(107 citation statements)
references
References 34 publications
24
69
8
6
Order By: Relevance
“…The authors have not found any published research on the effects of the characteristics of the rearing diets on egg quality to compare with the results reported herein. In regard to dietary energy, Grobas et al (1999b) and Pérez-Bonilla et al (2012a) observed similar egg quality (dirty, broken, shell-less, Haugh units, yolk pigmentation and yolk to albumen ratio) for hens fed diets containing 11.10 or 11.52 MJ AME n /kg, in agreement with the results reported herein. However, Zimmermann and Andrews (1987) and Wu et al (2005) observed a reduction in albumen quality and Junqueira et al (2006) a decrease in the percentage of shell-less eggs with increases in the energy concentration of the diet.…”
Section: Egg Qualitysupporting
confidence: 90%
See 1 more Smart Citation
“…The authors have not found any published research on the effects of the characteristics of the rearing diets on egg quality to compare with the results reported herein. In regard to dietary energy, Grobas et al (1999b) and Pérez-Bonilla et al (2012a) observed similar egg quality (dirty, broken, shell-less, Haugh units, yolk pigmentation and yolk to albumen ratio) for hens fed diets containing 11.10 or 11.52 MJ AME n /kg, in agreement with the results reported herein. However, Zimmermann and Andrews (1987) and Wu et al (2005) observed a reduction in albumen quality and Junqueira et al (2006) a decrease in the percentage of shell-less eggs with increases in the energy concentration of the diet.…”
Section: Egg Qualitysupporting
confidence: 90%
“…The decrease in ADFI observed in hens fed the high energy diet was expected because poultry eat to satisfy their energy requirements, provided that the capacity of the GIT is not compromised (Hill et al, 1956;Leeson et al, 1997). Egg production and egg size were not affected by the energy content of the diet, consistent with data of Grobas et al (1999b) in brown hens Fig. 3.…”
Section: Laying Phase Dietssupporting
confidence: 81%
“…This may be explained by the higher feed intake of the birds fed higher energy levels, according to the experimental treatments. The results of the present experiment disagree with the findings of Grobas et al (1999), Wu et al (2007) and Valkonen et al (2008), who fed layers different dietary ME levels and observed an improvement (P<0.05) in feed conversion ratio as the dietary ME increased. On the other hand, Grobas et al (1999) and evaluated the effect of the intake of feeds containing different energy levels on the egg production of layers and concluded that feed conversion ratio was not influenced (P>0.05) by the dietary energy level; however, feed was offered ad libitum in these experiments.…”
Section: Resultscontrasting
confidence: 99%
“…The results of the present experiment disagree with the findings of Grobas et al (1999), Wu et al (2007) and Valkonen et al (2008), who fed layers different dietary ME levels and observed an improvement (P<0.05) in feed conversion ratio as the dietary ME increased. On the other hand, Grobas et al (1999) and evaluated the effect of the intake of feeds containing different energy levels on the egg production of layers and concluded that feed conversion ratio was not influenced (P>0.05) by the dietary energy level; however, feed was offered ad libitum in these experiments. The differences in feed conversion ratio results per kg and per dozen eggs may be due to the energy levels used in the different studies because, when energy supply is higher than the nutritional requirements of birds, there are no improvements in egg production, egg mass or feed conversion ratio; however, the energy surplus may be stored in the body, increasing body weight and body fat content.…”
Section: Resultscontrasting
confidence: 99%
“…Feed intake is higher in low energy diet and lower in high energy diet. Hens fed with 1,848 kcal productive energy consumed 9.7% more feed than the hens provided with 2,046 kcal productive energy per kg of feed (Hill et al, 1956), increased in energy from 2,680 kcal to 2,810 kcal of ME/kg, and decreased the feed intake by 4% (Grobas et al, 1999). Similarly, Harms et al (2000) concluded that the hens fed with 2,519 kcal of ME/kg consumed 8.5% more feed than the hens fed with 2,798 kcal of ME/kg diet, and hens fed with 3,078 kcal of ME/kg diet consumed 3% less feed compared to the hens fed with 2,798 kcal of ME/kg diet.…”
Section: Introductionmentioning
confidence: 97%